Information Extraction from Heterogeneous WWW Resources - Sulong, Muhammad Suhaizan; Meziane, Farid (2004)
The information available on the WWW is growing very fast. However, a fundamental problem with the information on the WWW is its lack of structure making its exploitation very difficult. As a result, the desired information is getting more difficult to retrieve and extract. To overcome this problem many tools and techniques are being developed and used for locating the web pages of interest and extracting the desired information from these pages. In this paper we present the first prototype of an Information Extraction (IE) system that attempts to extract information on different Computer Science related courses offered by British Universities.